77 Shadow Street [compact disc, unabridged] : a novel - Koontz, Dean R. (Dean Ray), 1945- (Brilliance Audio, 2011)
Enter the world of the Pendleton, a beautiful limestone Gilded Age palace that's been converted into a set of highly desirable condominiums. Its tenants feel lucky to live there. Yet luck and the Pendleton have little in common; its years have been colored by madness, kidnappings, murder, and strange, inexplicable accidents.